IDENTIFICATION OF HALAL CRITICAL CONTROL POINTS IN THE LEATHER TANNING PROCESS FOR HALAL LEATHER MATERIAL PRODUCTION - Dian Nur Amalia; Swatika Juhana (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2026)
The expansion of the halal concept beyond the food and beverage sector has increased attention toward halal compliance in non-edible industries, including leather manufacturing. Leather processing involves multiple stages, namely beamhouse operations, tanning, post-tanning, and finishing, all of which must comply with the Halal Product Assurance System (SJPH). Within this framework, halal assurance encompasses not only the final product but also raw materials, processing aids, production facilities, storage, distribution, and documentation systems. This study aims to systematically identify halal critical control points throughout the leather tanning process based on the SJPH framework. A qualitative approach was employed through field observations at the Leather Processing Technology Department of Politeknik ATK Yogyakarta and an extensive literature review. The results indicate that critical halal risks primarily arise from the origin and death status of animals at the raw material stage, the use of chemical auxiliaries during beamhouse to finishing processes, and the potential for cross-contamination within production facilities and waste management systems. High-risk inputs include enzymes, surfactants, retanning agents, fatliquors, and finishing materials potentially derived from non-halal sources. These findings underscore the necessity of an integrated, documented, and consistently implemented SJPH to ensure halal integrity across the leather production chain.